Modelagem de atributos químicos e espectrais dos solos de Feira de Santana-Ba - Santos, Jonathas Jesus dos (2019)
Currently the demand of the consumer market on agricultural products is increasing, these conditions allied to other factors such as soil erosion, nutrient loss, organic matter reduction, salinization, compaction, among others, has been making research on spatial variability of soil elements is a subject of great relevance. In many recent studies, the application of remote sensing and geostatistics techniques to the evaluation of soil attributes and their content of larger elements has attracted attention, precisely because these techniques can generate fast and accurate information, gaining credibility in the scientific community. In this scenario, the following question arises: Is it possible to evaluate such soil attributes using spectroradiometry with precision and low cost? In this perspective, this work has the general objective: To model chemical and spectral attributes present in the soils of Feira de Santana-BA. With the specific objectives, it was intended to model the natural chemical characteristics of the major elements of Phosphorus (P), Potassium (K), Magnesium (Mg), Calcium (Ca), and Sodium to correlate the chemical elements with the spectral response of the soils and to identify, by spectroradiometry, mineralogical attributes of the soils of Feira de Santana-BA. For the modeling of chemical and spectral attributes present in the soils, soil samples were collected initially in the study area.The chemical analysis of the collected samples was carried out, determining the content of the major elements P, K, Mg, Ca, and Na, as well as an exploratory study in the results of the analyzes, such as descriptive statistics, removal of outliers, frequency distribution , interpolator definition and pixel size. The experimental semivariograms were adjusted with the chemical results and soon afterwards the ordinary Kriging for each element was adopted adopting Embrapa standards. Afterwards, the spectroradiometric evaluation of the samples was carried out by extracting the reflectance data, continuous removed and depths of the bands 500, 600, 950, 1400, 1900, 2205, 2300, 2380 and 2445 nanometers, also identifying the minerals present with characteristic features. The correlation between the data extracted from the bands and the major elements of the Feira de Santana-Ba soils was then evaluated by the Pearson correlation coefficient. It was observed that the distributions of the elements P, K, Mg, Ca, and Na occur in a differentiated form in the space. It was verified that there is a low linear correlation between the spectra and the soil chemistry and that the main minerals in the soils of Feira de Santana are Goethina, Caulinita, Muscovite, Montmorillonite and Ilite